Some thoughts and proposals for a way forward - Campos, Adriana; Piñeiro, Valeria; Piñeiro, Martín (Instituto Interamericano de Cooperación para la Agricultura, 2021)
The WTO XII Ministerial Conference (MC12) will be a different and singular event for the organization and also for the participating member countries. It is an extraordinary opportunity to take a fresh look to trade matters, in extremely difficult and rapidly changing times, and move forward with new ideas and proposals.